Makna Solitary Life dari Buku the Spiritual World of Isaac the Syrian - Dame hati Gulo; Hendi Hendi (Integritas: Jurnal Teologi, 2022)
This article examines the important meaning of solitary life from the book The Spiritual World of Isaac the Syrian in human life, especially for Christians today. The author explains the benefits and goals of solitary life in human life, namely how one's relationship with God is intimate and personal. This research method is a literature study by analyzing books and collecting various other sources from journal articles related to the topic of this article. The author concludes that according to Isaac, solitary life helps each person to be close, enjoy, feel, and experience God personally. By living solitary the intimate experience with God deepens. In addition, solitary life can not only be done in certain places, but wherever and whenever and anyone can feel and enjoy God through hasychasm, prayer in the heart, God's love and purification of the soul so that they are getting closer to God every day.